The Clinical and Radiological Spectrum of Hippocampal Pathology in Amyotrophic Lateral Sclerosis - Christidi, Foteini; Karavasilis, Efstratios; Velonakis, Georgios; Ferentinos, Panagiotis; Rentzos, Michail; Kelekis, Nikolaos; Evdokimidis, Ioannis; Bede, Peter (Frontiers in Neurology, 2018)
Hippocampal pathology in Amyotrophic Lateral Sclerosis (ALS) remains surprisingly under recognized despite compelling evidence from neuropsychology, neuroimaging and neuropathology studies. Hippocampal dysfunction contributes significantly to the clinical heterogeneity of ALS and requires structure-specific cognitive and neuroimaging tools for accurate in vivo evaluation. Recent imaging studies have generated unprecedented insights into the presymptomatic and longitudinal processes affecting this structure and have contributed to the characterisation of both focal and network-level changes. Emerging neuropsychological data suggest that memory deficits in ALS may be independent from executive dysfunction. In the era of precision medicine, where the development of individualized care strategies and patient stratification for clinical trials is a priority, the comprehensive review of hippocampal dysfunction in ALS is particularly timely.